Magnesium batteries: Current state of the art, issues and future perspectives - Mohtadi, Rana; Mizuno, Fuminori (Beilstein Journal of Nanotechnology, 2014)
“...each metal has a certain power, which is different from metal to metal, of setting the electric fluid in motion...” Count Alessandro Volta. Inspired by the first rechargeable magnesium battery prototype at the dawn of the 21st century, several research groups have embarked on a quest to realize its full potential. Despite the technical accomplishments made thus far, challenges, on the material level, hamper the realization of a practical rechargeable magnesium battery. These are marked by the absence of practical cathodes, appropriate electrolytes and extremely sluggish reaction kinetics. Over the past few years, an increased interest in this technology has resulted in new promising materials and innovative approaches aiming to overcome the existing hurdles. Nonetheless, the current challenges call for further dedicated research efforts encompassing fundamental understanding of the core components and how they interact with each other to offering new innovative solutions. In this review, we seek to highlight the most recent developments made and offer our perspectives on how to overcome some of the remaining challenges.
Keywords: cathode; electrolyte; magnesium anode; magnesium battery; magnesium metal

Handbook of Batteries - Linden, D.; Reddy, T. B. (McGraw-Hill, 2011)

Encyclopædia Britannica: Conte Alessandro Volta

Hidden History: Lost Civilizations, Secret Knowledge, and Ancient Mysteries - Haughton, B. (The Baghdad battery, 2007)

(untitled) - Dunn, B.; Kamath, H.; Tarascon, J.-M. (Science, 2011)

(untitled) - Xu, K. (Chem. Rev., 2004)

(untitled) - Kim, H.; Jeong, G.; Kim, Y.-U.; Kim, J.-H.; Park, C.-M.; Sohn, H.-J. (Chem. Soc. Rev., 2013)

(untitled) - Yoo, H.-D.; Shterenberg, I.; Gofer, Y.; Gershinsky, G.; Pour, N.; Aurbach, D. (Energy Environ. Sci., 2013)

(untitled) - Muldoon, J.; Bucur, C. B.; Oliver, A. G.; Sugimoto, T.; Matsui, M.; Kim, H. S.; Allred, G. D.; Zajicek, J.; Kotani, Y. (Energy Environ. Sci., 2012)

(untitled) - Aurbach, D.; Weissman, I.; Gofer, Y.; Levi, E. (Chem. Rec., 2003)

Lithium Batteries: Advanced Technologies and Applications - Gofer, Y.; Pour, N.; Aurbach, D. (Electrolytic solutions for rechargeable magnesium batteries, 2013)

(untitled) - Lu, Z.; Schechter, A.; Moshkovich, M.; Aurbach, D. (J. Electroanal. Chem., 1999)

(untitled) - Gregory, T. D.; Hoffman, R. J.; Winterton, R. C. (J. Electrochem. Soc., 1990)

(untitled) - Matsui, M. (J. Power Sources, 2011)

(untitled) - Arthur, T. S.; Singh, N.; Matsui, M. (Electrochem. Commun., 2012)

(untitled) - Singh, N.; Arthur, T. S.; Ling, C.; Matsui, M.; Mizuno, F. (Chem. Commun., 2013)

(untitled) - Shao, Y.; Gu, M.; Li, X.; Nie, Z.; Zuo, P.; Li, G.; Liu, T.; Xiao, J.; Cheng, Y.; Wang, C.; Zhang, J.-G.; Liu, J. (Nano Lett., 2014)

(untitled) - Park, M. H.; Kim, M. G.; Joo, J.; Kim, K.; Kim, J.; Ahn, S.; Cui, Y.; Cho, J. (Nano Lett., 2009)

(untitled) - Magasinski, A.; Dixon, P.; Hertzberg, B.; Kvit, A.; Ayala, J.; Yushin, G. (Nat. Mater., 2010)

(untitled) - Muldoon, J.; Bucur, C. B.; Oliver, A. G.; Zajicek, J.; Allred, G. D.; Boggess, W. C. (Energy Environ. Sci., 2013)

(untitled) - Aurbach, D.; Lu, Z.; Schechter, A.; Gofer, Y.; Gizbar, H.; Turgeman, R.; Cohen, Y.; Moshkovich, M.; Levi, E. (Nature, 2000)

(untitled) - Aurbach, D.; Gofer, Y.; Lu, Z.; Schechter, A.; Chusid, O.; Gizbar, H.; Cohen, Y.; Ashkenazi, V.; Moshkovich, M.; Turgeman, R.; Levi, E. (J. Power Sources, 2001)

(untitled) - Aurbach, D.; Gizbar, H.; Schechter, A.; Chusid, O.; Gottlieb, H. E.; Gofer, Y.; Goldberg, I. (J. Electrochem. Soc., 2002)

(untitled) - Aurbach, D.; Suresh, G. S.; Levi, E.; Mitelman, A.; Mizrahi, O.; Chusid, O.; Brunelli, M. (Adv. Mater., 2007)

(untitled) - Kim, H. S.; Arthur, T. S.; Allred, G. D.; Zajicek, J.; Newman, J. G.; Rodnyansky, A. E.; Oliver, A. G.; Boggess, W. C.; Muldoon, J. (Nat. Commun., 2011)

(untitled) - Liebenow, C.; Yang, Z.; Lobitz, P. (Electrochem. Commun., 2000)

(untitled) - Guo, Y. S.; Zhang, F.; Yang, J.; Wang, F. F.; NuLi, Y. N.; Hirano, S. I. (Energy Environ. Sci., 2012)

(untitled) - Mohtadi, R.; Matsui, M.; Arthur, T. S.; Hwang, S. J. (Angew. Chem., Int. Ed., 2012)
J. Angew. Chem. 2012, 124, 9918.

(untitled) - Shao, Y. Y.; Liu, T. B.; Li, G. S.; Gu, M.; Nie, Z. M.; Engelhard, M. H.; Xiao, J.; Lv, D. P.; Wang, C. M.; Zhang, J. G.; Liu, J. (Sci. Rep., 2013)

(untitled) - Wang, F. F.; Guo, Y. S.; Yang, J.; Nuli, Y.; Hirano, S. (Chem. Commun., 2012)

(untitled) - Nelson, E. G.; Kampf, J. W.; Bartlett, B. M. (Chem. Commun., 2013)

(untitled) - Liao, C.; Guo, B.; Jiang, D.; Custelcean, R.; Mahurin, S. M.; Sun, X.-G.; Dai, S. (J. Mater. Chem. A, 2014)

(untitled) - Zhao-Karger, Z.; Zhao, X.; Fuhr, O.; Fichtner, M. (RSC Adv., 2013)

(untitled) - Doe, R. E.; Han, R.; Hwang, J.; Gmitter, A. J.; Shterenberg, I.; Yoo, H. D.; Pour, N.; Aurbach, D. (Chem. Commun., 2014)

(untitled) - Liu, T.; Shao, Y.; Li, G.; Gu, M.; Hu, J.; Xu, S.; Nie, Z.; Chen, X.; Wang, C.; Liu, J. (J. Mater. Chem. A, 2014)

(untitled) - Carter, T. J.; Mohtadi, R.; Arthur, T. S.; Mizuno, F.; Zhang, R.; Shirai, S.; Kampf, J. W. (Angew. Chem., Int. Ed., 2014)

(untitled) - Chusid, O.; Gofer, Y.; Gizbar, H.; Vestfrid, Y.; Levi, E.; Aurbach, D.; Riech, I. (Adv. Mater., 2003)

(untitled) - Higashi, S.; Miwa, K.; Aoki, M.; Takechi, K. (Chem. Commun., 2013)

(untitled) - Connor, J. H.; Reid, W. E., Jr; Wood, G. B. (J. Electrochem. Soc., 1957)

(untitled) - Cheek, G. T.; O'Grady, W. E.; El Abedin, S. Z.; Moustafa, E. M.; Endres, F. (J. Electrochem. Soc., 2008)

(untitled) - Yoshimoto, N.; Matsumoto, M.; Egashia, M.; Morita, M. (J. Power Sources, 2010)

(untitled) - NuLi, Y.; Yang, J.; Wu, R. (Electrochem. Commun., 2005)

(untitled) - Amir, N.; Vestfrid, Y.; Chusid, O.; Gofer, Y.; Aurbach, D. (J. Power Sources, 2007)

(untitled) - Viestfrid, Yu.; Levi, M. D.; Gofer, Y.; Aurbach, D. (J. Electroanal. Chem., 2005)

(untitled) - Aurbach, D.; Turgeman, R.; Chusid, O.; Gofer, Y. (Electrochem. Commun., 2001)

(untitled) - Arthur, T. S.; Glans, P.-A.; Matsui, M.; Zhang, R.; Ma, B.; Guo, J. (Electrochem. Commun., 2012)

(untitled) - Benmayza, A.; Ramanathan, M.; Arthur, T. S.; Matsui, M.; Mizuno, F.; Guo, J.; Glans, P.-A.; Prakash, J. (J. Phys. Chem. C, 2013)

(untitled) - Kumar, G. G.; Munichandraiah, N. (Electrochim. Acta, 1999)

(untitled) - Morita, M.; Yoshimoto, N.; Yakushiji, S.; Ishikawa, M. (Electrochem. Solid-State Lett., 2001)

(untitled) - Pandey, G. P.; Agrawal, R. C.; Hashmi, S. A. (J. Solid State Electrochem., 2011)

(untitled) - Aubrey, M. L.; Ameloot, R.; Wiers, B. M.; Long, J. R. (Energy Environ. Sci., 2014)

(untitled) - Ikeda, S.; Takahashi, M.; Ishikawa, J.; Ito, K. (Solid State Ionics, 1987)

(untitled) - Kawamura, J.; Morota, K.; Kuwata, N.; Nakamura, Y.; Maekawa, H.; Hattori, T.; Imanaka, N.; Okazaki, Y.; Adachi, G.-y. (Solid State Commun., 2001)

(untitled) - Matsuo, M.; Oguchi, H.; Sato, T.; Takamura, H.; Tsuchida, E.; Ikeshoji, T.; Orimo, S. (J. Alloys Compd., 2013)

(untitled) - Unemoto, A.; Matsuo, M.; Orimo, S.-I. (Adv. Funct. Mater., 2014)

(untitled) - Makino, K.; Katayama, Y.; Miura, T.; Kishi, T. (J. Power Sources, 2001)

(untitled) - NuLi, Y.; Yang, J.; Wang, J.; Li, Y. (J. Phys. Chem. C, 2009)

(untitled) - NuLi, Y.; Yang, J.; Li, Y.; Wang, J. (Chem. Commun., 2010)

(untitled) - Ling, C.; Banerjee, D.; Song, W.; Zhang, M.; Matsui, M. (J. Mater. Chem., 2012)

(untitled) - Liu, B.; Luo, T.; Mu, G.; Wang, X.; Chen, D.; Shen, G. (ACS Nano, 2013)

(untitled) - NuLi, Y.; Guo, Z.; Liu, H.; Yang, J. (Electrochem. Commun., 2007)

(untitled) - Li, W.; Li, C.; Zhou, C.; Ma, H.; Chen, J. (Angew. Chem., Int. Ed., 2006)

(untitled) - Khoo, T.; Somers, A.; Torriero, A. A. J.; MacFarlane, D. R.; Howlett, P. C.; Forsyth, M. (Electrochim. Acta, 2013)

(untitled) - Shiga, T.; Hase, Y.; Kato, Y.; Inoue, M.; Takechi, K. (Chem. Commun., 2013)

(untitled) - Sutto, T. E.; Duncan, T. T. (Electrochim. Acta, 2012)

(untitled) - Sutto, T. E.; Duncan, T. T. (Electrochim. Acta, 2012)

(untitled) - Ichitsubo, T.; Adachi, T.; Yagi, S.; Doi, T. (J. Mater. Chem., 2011)

(untitled) - Bruce, P. G.; Krok, F.; Nowinski, J.; Gibson, V. C.; Tavakkoli, K. (J. Mater. Chem., 1991)

(untitled) - Novák, P.; Desilvestro, J. (J. Electrochem. Soc., 1993)

(untitled) - Novák, P.; Imhof, R.; Haas, O. (Electrochim. Acta, 1999)

(untitled) - Imamura, D.; Miyayama, M.; Hibino, M.; Kudo, T. (J. Electrochem. Soc., 2003)

(untitled) - Imamura, D.; Miyayama, M. (Solid State Ionics, 2003)

(untitled) - Amatucci, G. G.; Badway, F.; Singhal, A.; Beaudoin, B.; Skandan, G.; Bowmer, T.; Plitz, I.; Pereira, N.; Chapman, T.; Jawaorski, R. (J. Electrochem. Soc., 2001)

(untitled) - Levi, E.; Gofer, Y.; Aurbach, D. (Chem. Mater., 2010)

(untitled) - Liang, Y.; Feng, R.; Yang, S.; Ma, H.; Liang, J.; Chen, J. (Adv. Mater., 2011)

(untitled) - Yang, S.; Li, D.; Zhang, T.; Tao, Z.; Chen, J. (J. Phys. Chem. C, 2012)

(untitled) - Liu, Y.; Jiao, L.; Wu, Q.; Du, J.; Zhao, Y.; Si, Y.; Wang, Y.; Yuan, H. (J. Mater. Chem. A, 2013)

(untitled) - Tao, Z.-L.; Xu, L.-N.; Gou, X.-L.; Chen, J.; Yuan, H.-T. (Chem. Commun., 2004)

(untitled) - Kumagai, N.; Komaba, S.; Sakai, H.; Kumagai, N. (J. Power Sources, 2001)

(untitled) - Rasul, S.; Suzuki, S.; Yamaguchi, S.; Miyayama, M. (Solid State Ionics, 2012)

(untitled) - Rasul, S.; Suzuki, S.; Yamaguchi, S.; Miyayama, M. (Electrochim. Acta, 2012)

(untitled) - Zhang, R.; Yu, X.; Nam, K.-W.; Ling, C.; Arthur, T. S.; Song, W.; Knapp, A. M.; Ehrlich, S. N.; Yang, X.-Q.; Matsui, M. (Electrochem. Commun., 2012)

(untitled) - Ling, C.; Mizuno, F. (Chem. Mater., 2013)